The Relationship between Attitude and Speaking Proficiency of Iranian EFL Learners: The Case of Darrehshehr City. (3rd August 2015) - Zeinivand, Tayebeh; Azizifar, Akbar; Gowhary, Habib
Abstract: Among different factors contributing to foreign language learning, affective variables such as attitudes, orientations, motivation, and anxiety are of paramount importance. Among these various factors, learners' attitude towards language learning is considered as one of the key factors in motivating the learners to learn that language. The present study investigates the correlation between attitude and speaking proficiency in the Iranian EFL context. The sample of the study consists of 70 EFL learners from three Institutions in the city of Darrehshahr. The Data were collected through using Gardner's Attitude/Motivation Test Battery Questionnaire and speaking Proficiency Test to assess the English speaking proficiency level. Means, S.D., percentage, Pearson product moment correlations, and Kolmogorov –Smirnov Test were used to analyze the data. The analyses revealed that EFL learners have very high attitude towards learning English and relationship between attitude and speaking proficiency learners is positive. The paper also reported some implications of the study.